2020
DOI: 10.1590/s1983-41952020000600011
|View full text |Cite
|
Sign up to set email alerts
|

Metal magnesium industry waste for partial replacement of Portland cement

Abstract: The high demand for concrete has triggered studies on the mitigation of Portland cement production impacts, such as greenhouse gas emissions and energy demands, in addition to enabling cost reduction. Partial replacement of cement with other materials has been employed as an alternative to minimize the damage caused by the cement industry. In this regard, it is necessary to use materials that efficiently replace cement clinker. This study uses waste generated from the production of metallic magnesium as a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…New concrete mixes and concepts are being developed across the world [41,42,44,[51][52][53][54] for meeting sustainable infrastructure demands or to attain novel properties, and few studies are reported for India as well [55][56][57]. This could even include fibre-reinforced concrete (both natural [58,59] and artificial: basalt nano-fibre [60]; steel fibre [56]), recycled aggregate concrete [61], and carbon nanotube reinforced concrete [62], among others.…”
Section: Generation Of Fire/elevated Temperature Test Data For Indianmentioning
confidence: 99%
“…New concrete mixes and concepts are being developed across the world [41,42,44,[51][52][53][54] for meeting sustainable infrastructure demands or to attain novel properties, and few studies are reported for India as well [55][56][57]. This could even include fibre-reinforced concrete (both natural [58,59] and artificial: basalt nano-fibre [60]; steel fibre [56]), recycled aggregate concrete [61], and carbon nanotube reinforced concrete [62], among others.…”
Section: Generation Of Fire/elevated Temperature Test Data For Indianmentioning
confidence: 99%